VEGF and eNOS genes polymorphism features in patients with diabetes mellitus with and without initial non-proliferative diabetic retinopathy - A. V. Shevchenko; V. F. Prokof`ev; V. I. Konenkov; V. V. Klimontov; D. V. Chernykh; A. N. Trunov; A. V. Eremina; V. V. Chernykh (Acta Biomedica Scientifica)
The endothelial NO synthase (eNOS) and vascular endothelial growth factor (VEGF) imbalance and the polymorphism of these genes may be the predisposition for diabetic retinopathy (DR) development and progression.The aim: to analyze VEGF (rs699947 and rs3025039) and eNOS (rs2070744) genes polymorphism and their combinations in patients with type 2 diabetes mellitus (DM2) with and without initial non-proliferative DR.Materials and methods. The study included 200 patients with type 2 diabetes (155 women and 45 men, age – 43–70 years): 111 people without and 89 people with DR. The polymorphism of the regulatory regions of VEGF (rs699947 and rs3025039) and eNOS (rs2070744) genes was studied using restriction fragment length polymorphism analysis and TaqMan Real-Time PCR by. Statistical processing was carried out using the software packages Statistica 10.0, SPSS Statistics 23 and the package of original programs for volumetric processing of bioinformation.Results. The VEGF-2578 heterozygosity and two complex genotypes – VEGF-2578CA:VEGF+936CC and NOS3-786CT:VEGF-2578CA:VEGF+936CC – signifi cantly decreased in patients with DR. The predisposition to early DR development to minor genotype of eNOS gene in the NOS3-786CC:VEGF+936CT complex and signifi cantly decreased the homozygous wild-type eNOS genotype in DM2 patients with ophthalmopathology were shown. NOS3-86TT:VEGF2578AA genotype signifi cantly decreased in group with retinopathy developing and the glycated hemoglobin high level.Conclusion. Along with the clinical risk factors for the development of DR in DM2, the genetic polymorphism of the regulatory regions of the genes analyzed by us has a signifi cant weight. When analyzing potential genetic markers, it is important to consider possible joint epistatic/hypostatic effects. The complex analysis of polymorphic gene can help early prognosis of the DR development.